(untitled) (Journal of Economic Research & Business Administration, 2016)
More than 30 years have passed since the Chinese economic reforms. This is a considerable period, which requires generalization and summa rizing. The study of the theoretical beginning of reforms in the economic system of China, one of the fundamental painstaking works that has been done by scientific economists of the country that focus on finding the goals, strategies and tactics of reform, adequate to the national circumstances, taking into account the analysis and development of the global economic studies aimed at identifying the specifics of the Chinese model of socioeconomic modernization. Success of economic reform in China serves as a stimulus for Chinese scholars to develop their own theory of transition to a market that differs from the neoclassical concepts underlying the “shock” model of market transformation.